Mod en neutral seksualitet! eller Roland Barthes som queerteoretiker? - Leer, Jonatan (Passage - Tidsskrift for litteratur og kritik, 2013)
Jonatan Leer: “Towards a Neutral Sexuality! or Roland Barthes as a Queer Thinker?” This article argues that the work of Roland Barthes has interesting perspectives in common with queer theory. This argument is put forward by using his concept of ‘the neutral’ that Barthes defines as “that which outplays the paradigm”. This notion was presented at a series of lectures at Collège de France in 1977. Through a reading of Barthes’ autobiography, Roland Barthes par Roland Barthes (1975), the article demonstrates how Barthes tries to outplay the paradigms that rule over the hegemonic understanding of gender and sexuality. Furthermore, the fragmented text presents a vision of a sexual utopia, a neutral sexuality, that tries – like queer theory – to go and think beyond a binary conception of gender and sexuality. Finally, it is suggested that we should start to think about a movement of “French queer theory” in the late 1970’s that beside Barthes includes Jean Baudrillard.